Karantina Wilayah sebagai Ide Penciptaan Foto Seri Tentang Topical Trends Covid-19 - Pamungkas Wahyu Setiyanto; Novan Jemmi Andrea; Agus Triyana (Institut Seni Indonesia Yogyakarta, 2021)
Quarantine Areas as an Idea The Creation of A Series of Topical Trends of Covid-19. Research called quarantine areas as an idea the creation of a photograph series about topical trends covid-19 is a study based the creation of artistic, with the result of a photograph series describing the atmosphere quarantine areas due to pandemics covid-19 in Pedukuhan Pelem Sewu , RT 08 and RT 09 , Panggungharjo, Sewon, Bantul , Yogyakarta. Photo series made is activity the creation of a guide making a photograph produce a series of photos containing descriptions based on the theme or a particular subject same, that is the situation quarantine areas. Through the observation, design concept, to recording equipment, produced a series of photographs quarantine areas described the situation, the closure enter and leave in a region in which there were people infected covid-19. Methods used in this study began of observation, the design of the concept of, until shooting. The result of the creation of this series are photographs that describe scenes of residents and the activities of that lasts for quarantine areas to come into effect. Conclusions obtained from the research with the approach the work of art it produces an understanding of the circumstances and the residents habit covid-19 due to new pandemic. A new habit of them is online learning activity, aware of their health and clean environment, and of their fellow citizens for mutual support and through the quarantine.